2019
DOI: 10.1021/acsabm.9b00754
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of Graphene Oxide–Copper Oxide Nanoparticle Nanocomposites

Abstract: The resistance of pathogenic bacteria toward traditional biocidal treatment methods is a growing concern in various settings, including that of water treatment and in the medical industry. As such, advanced antibacterial technologies are needed to prevent infections, against which current antibiotics are failing. This study introduces copper oxide nanoparticles (CuONPs) doped in graphene oxide (GO) as a potential pathogenic bacterial treatment. The aim of the study was to evaluate the antibacterial properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 63 publications
2
35
0
Order By: Relevance
“…A few studies have also been devoted to investigating the antibacterial action of Cu [69], Cu 2 O [70,71] or CuO [72] nanoparticles bound to GO or rGO. At high concentrations, these nanomaterials are toxic to the majority of microorganisms since the redox properties of Cu provoke cellular damage including protein and lipid oxidation.…”
Section: Nanocomposites With Cooper Oxide Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies have also been devoted to investigating the antibacterial action of Cu [69], Cu 2 O [70,71] or CuO [72] nanoparticles bound to GO or rGO. At high concentrations, these nanomaterials are toxic to the majority of microorganisms since the redox properties of Cu provoke cellular damage including protein and lipid oxidation.…”
Section: Nanocomposites With Cooper Oxide Nanoparticlesmentioning
confidence: 99%
“…Nanocomposites of CuO nanoparticles and GO have also been developed [72], which were found to be effective antibacterial nanomaterials, strongly inhibiting the proliferation of both E. coli and S. typhimurium bacteria compared to GO or CuO alone. The surface morphology of the nanocomposite significantly differed from that of the pure components (Figure 8), as revealed by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and atomic force microscopy (AFM), and this could account for the improved bactericide action.…”
Section: Nanocomposites With Cooper Oxide Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the ionic liquid increases the graphene dispersion; therefore, the G–Cu NPs are better dispersed into the silicon sample allowing a better antimicrobial response. It is reported that the antimicrobial effect of Cu is based on the copper nanoparticles acting on the enzymes of the cell membrane of bacteria affecting their respiratory function [ 49 , 50 ]. Thus, having a better dispersion of the G/Cu particles induced by the ionic liquid, a greater possibility of interaction of the particles with bacteria and this in turn would be reflected in a greater antimicrobial effect [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the top‐down synthesis of graphene‐based nanomaterials, the starting material is usually some form of bulk graphite and then broken down through physical or chemical processes, where exfoliation ultimately results in the production of small graphitic carbon consisting of a varied number of graphene layers. One such top‐down method is known as the Hummers’ method, [22,23] in which graphite flakes or pitch carbon fiber can be broken down through chemical oxidation using concentrated acids, resulting in the formation of GO. Depending on the degree of oxidation, controlled through reaction temperature, time, and acid concentration, one can obtain GO with sizes varied from several hundred nanometers down to the quantum dot regime of only a few nanometers in diameter [14,24–27] .…”
Section: Introductionmentioning
confidence: 99%